Lipoprotein(a) Particle Production as a Determinant of Plasma Lipoprotein(a) Concentration Across Varying Apolipoprotein(a) Isoform Sizes and Background Cholesterol‐Lowering Therapy. Issue 7 (2nd April 2019) - Chan, Dick C.; Watts, Gerald F.; Coll, Blai; Wasserman, Scott M.; Marcovina, Santica M.; Barrett, P. Hugh R.
Abstract : Background: Elevated lipoprotein(a) (Lp(a)), a low‐density lipoprotein‐like particle bound to the polymorphic apolipoprotein(a) (apo(a)), may be causal for cardiovascular disease. However, the metabolism of Lp(a) in humans is poorly understood. Methods and Results: We investigated the kinetics of Lp(a)‐apo(a) and low‐density lipoprotein‐apoB‐100 in 63 normolipidemic men. The fractional catabolic rate (FCR) and production rate PR) were studied. Plasma apo(a) concentration was significantly and inversely associated with apo(a) isoform size ( r =−0.536, P <0.001) and apo(a) FCR ( r =−0.363, P <0.01), and positively with apo(a) PR ( r =0.877, P <0.001). There were no significant associations between the FCRs of apo(a) and low‐density lipoprotein‐apoB‐100. Subjects with smaller apo(a) isoform sizes (≤22 kringle IV repeats) had significantly higher apo(a) PR ( P <0.05) and lower apo(a) FCR ( P <0.01) than those with larger sizes. Plasma apo(a) concentration was significantly associated with apo(a) PR ( r =0.930, P <0.001), but not with FCR ( r =−0.012, P >0.05) in subjects with smaller apo(a) isoform size. In contrast, both apo(a) PR and FCR were significantly associated with plasma apo(a) concentrations ( r =0.744 and −0.389, respectively, P <0.05) in subjects with larger isoforms. In multiple regression analysis, apo(a) PR and apo(a) isoform size were significant predictors of plasma apo(a) concentration independent of low‐density lipoprotein‐apoB‐100 FCR and background therapy with atorvastatin and evolocumab. Conclusions: In normolipidemic men, the plasma Lp(a) concentration is predominantly determined by the rate of production of Lp(a) particles, irrespective of apo(a) isoform size and background therapy with a statin and a proprotein convertase subtilisin‐kexin type 9 inhibitor. Our findings underscore the importance of therapeutic targeting of the hepatic synthesis and secretion of Lp(a) particles. Lp(a) particle catabolism may only play a modest role in determining Lp(a) concentration in subjects with larger apo(a) isoform size. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT02189837.